2015
DOI: 10.7314/apjcp.2015.16.8.3213
|View full text |Cite
|
Sign up to set email alerts
|

2-deoxy-D-Glucose Synergizes with Doxorubicin or L-Buthionine Sulfoximine to Reduce Adhesion and Migration of Breast Cancer Cells

Abstract: Background: Cancer metastasis depends on cell motility which is driven by cycles of actin polymerization and depolymerization. Reactive oxygen species (ROS) and metabolic oxidative stress have long been associated with cancer. ROS play a vital role in regulating actin dynamics that are sensitive to oxidative modification. The current work aimed at studying the effects of sub-lethal metabolic oxidative stress on actin cytoskeleton, focal adhesion and cell migration. Materials and Methods: T47D human breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…A study have showed that among breast cancer cell lines tested, SKBR3 was the most sensitive to the growth inhibitory effects of 2DG (Mustafa et al, 2015). In our study, the combination of 2DG and radiation, at different doses, caused cell killing and was significantly different from either treatment alone in both cell lines ( Figure 1B).…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…A study have showed that among breast cancer cell lines tested, SKBR3 was the most sensitive to the growth inhibitory effects of 2DG (Mustafa et al, 2015). In our study, the combination of 2DG and radiation, at different doses, caused cell killing and was significantly different from either treatment alone in both cell lines ( Figure 1B).…”
Section: Discussionsupporting
confidence: 55%
“…2DG-6-P is not a substrate for glucose-6-phosphate dehydrogenase or phosphohexoisomerase. Therefore, once formed, 2DG-6-P is not further metabolized, and, therefore, the output from glycolysis (ATP) and the pentose phosphate pathway gets reduced, and 2DG-6-P accumulates in the cell until dephosphorylated by phosphorylase (Maher et al, 2004;Pelicano et al, 2006;Dwarakanath, 2009;Aghaee et al, 2012;Mustafa et al, 2015). 2DG treatment resulted in intracellular ATP depletion as a consequence of glycolysis inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations